2004
DOI: 10.1152/ajplung.00171.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotrophin-1 alters airway smooth muscle structure and mechanical properties in airway explants

Abstract: Cardiotrophin-1 alters airway smooth muscle structure and mechanical properties in airway explants. Am J Physiol Lung Cell Mol Physiol 287: L1165-L1171, 2004. First published July 23, 2004 doi:10.1152/ ajplung.00171.2004.-Induction of hypertrophy and inhibition of apoptosis may be important mechanisms contributing to increased airway smooth muscle (ASM) mass in asthma. Data from our laboratory indicate that cardiotrophin-1 (CT-1) induces hypertrophy and inhibits apoptosis in isolated human ASM cells. To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…These data contrast with a previous study in which CT-1-treated airway explants showed increased smooth muscle mass but paradoxically reduced maximal isometric stress in response to acetylcholine (22), suggesting that hypertrophic muscle may not function normally. However, in the former study, CT-1 increased extracellular matrix deposition and passive tension, suggesting that the effects of CT-1 on contractility may have been counterbalanced by parallel increases in elastic load.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These data contrast with a previous study in which CT-1-treated airway explants showed increased smooth muscle mass but paradoxically reduced maximal isometric stress in response to acetylcholine (22), suggesting that hypertrophic muscle may not function normally. However, in the former study, CT-1 increased extracellular matrix deposition and passive tension, suggesting that the effects of CT-1 on contractility may have been counterbalanced by parallel increases in elastic load.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of peptide growth factors and bronchoconstrictor agonists have been shown to induce airway smooth muscle proliferation in vitro (20). More recently, cardiotrophin (CT)-1, a member of the IL-6 superfamily present in human lungs, has been shown to induce protein synthesis and cell enlargement, but not DNA synthesis, in cultured human bronchial smooth muscle cells (21) and guinea pig airway explants (22). In addition, we showed that transforming growth factor (TGF)-␤, a proasthmatic cytokine (23)(24)(25)(26), increased human bronchial smooth muscle cell size, protein synthesis, expression of ␣-smooth muscle actin and smooth muscle myosin heavy chain (smMHC), formation of actomyosin filaments, and cell shortening to acetylcholine (27).…”
mentioning
confidence: 99%
“…Our laboratory has shown that rat tracheal ASM responds to repeated allergen challenge with a reduced contractility of SM cells and a commensurate increase in SM cell number (17). Hypertrophy of ASM has also been shown to result in reduced contractility in some studies (18), although not consistently (19). Although detailed medication intake of the donors in the last weeks of life is difficult to get, it is possible that end-of-life drugs or asthma medication, particularly long-acting b-agonists, may have reduced contractility.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiotrophin increases the size and protein synthesis of cultured human bronchial smooth muscle cells (34). Cardiotrophin also increased the airway smooth muscle content of guinea pig airway explants (33). However, maximal isometric stress and perhaps shortening were decreased, suggesting that the contractile apparatus of hypertrophic airway smooth muscle cells may not be completely functional.…”
Section: Functional Effects Of Airway Smooth Muscle Proliferation Andmentioning
confidence: 99%